2007
DOI: 10.20885/psikologika.vol12.iss23.art5
|View full text |Cite
|
Sign up to set email alerts
|

Perilaku Proposal Etnis Jawa Dan Etnis Cina

Abstract: Purpose of this research is to compare prosocial behavior between two ethnics, Javaneese and Chineese. Hypotheses proposed that there's prosoclal behaviors differences between those two ethnic, theJavaneese prosociaf behavior is higer than Chineese. Subjects parl.icipated in this research were 184 Javaneese and Chineese who five in Jogjakarta. Prosocial behavior scale is used as the research tool.Data analyzed through two way Anova result F 13.048 with p <.01. This result proof that prosocial behavior between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
1
1
Order By: Relevance
“…It reflects that gender had no impact on prosocial behavior for this research. This result is intriguing because it contradicts with previous findings that emphasize important role of gender in prosocial behavior, with notion that female participants used to show higher score (Basti, 2007;Inglés et al, 2009;Muñoz Sánchez et al, 2004;Ongley & Malti, 2014;Oscar & Pohan, 2006). It can be assumed, based on this finding, that gender role might has not been developed by participants due to their ages.…”
Section: Discussioncontrasting
confidence: 73%
“…It reflects that gender had no impact on prosocial behavior for this research. This result is intriguing because it contradicts with previous findings that emphasize important role of gender in prosocial behavior, with notion that female participants used to show higher score (Basti, 2007;Inglés et al, 2009;Muñoz Sánchez et al, 2004;Ongley & Malti, 2014;Oscar & Pohan, 2006). It can be assumed, based on this finding, that gender role might has not been developed by participants due to their ages.…”
Section: Discussioncontrasting
confidence: 73%
“…Previous research conducted by Basti (2007), it was found that the prosocial behavior of Javanese and Chinese ethnic groups was in the high category. The research of Ibnu Munfaridz (2016) also aimed to determine the differences in prosocial behavior of Javanese and Bugis ethnic groups towards other ethnic groups.…”
Section: Introductionmentioning
confidence: 86%
“…Jejaring sosial merupakan salah satu faktor yang memengaruhi kemunculan pemberian amal (Putnam dalam Wang dan Graddy, 2008). Basti (2007) mengemukakan bahwa faktor yang memengaruhi perilaku prososial terdiri dari faktor internal dan faktor eksternal. Faktor internal terdiri dari karakteristik kepribadian, suasana hati, religiusitas pertimbangan untung rugi, kemampuan yang dimiliki, keuntungan pribadi, nilai dan norma-norma pribadi, empati dan jenis kelamin.…”
Section: Metodeunclassified